2015
DOI: 10.3923/std.2015.27.34
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and its Impacts on Growth of Blue Pine (Pinus wallichiana) in Murree Forest Division, Pakistan

Abstract: Climate change and its impacts were assessed on growth of Blue pine, Pinus wallichiana in Murree Forest Division. Change in temperature (maximum, minimum, mean) and precipitation was assessed for time period of 1963-2012 at 50×50 km 2 (0.5°×0.5°). Growth of P. wallichiana was measured in terms of ring-width, intra-ring early and late wood formation. The regime of maximum temperature, minimum temperature and mean temperature were estimated and found 26.45±0.08°C, 13.40±0.08°C and 19.90±0.07°C, respectively, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In additions, Sensula and Wilczynski,(2017) suggested that the surface temperature impacts on water-use efficiency in P. sylvestris and surged CO 2 emission is involved. The thickness of annual ring of P. wallichiana wassignificantly correlated with precipitation rate (Bajwa et al, 2015)and of P. sylvestris (Pritzkow et al, 2014)and particularly during June to July (Cedro , 2001), but not in all sites she inspected , notably so humid stands . Not in all times,here the positive impacts of precipitation and temperature on the growth of P. halepensis, P. pinaster , P. sylvestris even Fagus sylvatica, yet it is likely in the future, the rainfall impact on the growth (Sabate et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In additions, Sensula and Wilczynski,(2017) suggested that the surface temperature impacts on water-use efficiency in P. sylvestris and surged CO 2 emission is involved. The thickness of annual ring of P. wallichiana wassignificantly correlated with precipitation rate (Bajwa et al, 2015)and of P. sylvestris (Pritzkow et al, 2014)and particularly during June to July (Cedro , 2001), but not in all sites she inspected , notably so humid stands . Not in all times,here the positive impacts of precipitation and temperature on the growth of P. halepensis, P. pinaster , P. sylvestris even Fagus sylvatica, yet it is likely in the future, the rainfall impact on the growth (Sabate et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The impact of temperature on the growth of pine generally is significant in many studies and according to the model presented by Salminen and Jalkanen (2005), the increase of temperature by 1.0°C in July has brought about an increase in height by 1.8 cm in the next year in P. sylvestris. Bajwa et al (2015) found a positive, yet insignificant correlation between temperature with ring width and Hordo et al (2009) considered the temperature is the most important single agent in terms of growth activity for P. sylvestris, when they were tracing increment ring width extreme temperature, yet Gonzales-Benecke et al,(2017), in addition to temperature impact,stated that an elevated CO 2 contributed significantly in increase in the growth of P. taeda.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been conducted on these pine species from different parts of the Himalayas. Dendrochronological studies have also been carried out to determine the impact of climate change on growth of P. wallichiana (Bajwa et al, 2015). Similar work was conducted on P. roxburghii to understand age, structure, soil erosion, disturbance history and tree health (Speer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%